Psychosocial features of myocardial infarction patients and rehabilitation programs’ effectiveness - N. B. Lebedeva; O. V. Lebedev; N. I. Tarasov; E. Yu. Yakusheva; O. L. Barbarash (Кардиоваскулярная терапия и профилактика)
Aim. To investigate psychosocial factors and personality traits affecting the effectiveness of myocardial infarction (MI) rehabilitation programs. Material and methods. One hundred males with Q-wave MI, aged 35-73 (mean age 51.6±1.7 years), were examined. Standard clinical examination was combined with psychoemotional status assessment (Luscher test, SMIL questionnaire, Spielberger-Khanin State-Trait Anxiety Inventory, Jenkins Activity Survey on coronary behavior type, quality-of-life scales). One-half of the participants attended Coronary Club sessions, to modify behavioral risk factors for coronary heart disease. Results. The results obtained demonstrate high effectiveness of behavioral rehabilitation programs in MI patients. People with Type A coronary behavior had more complicated post-MI period, and more evident effectiveness of rehabilitation programs. Conclusion. Behavioral programs should be included into early complex rehabilitation of MI patients.